(untitled) (Annals of Medical Research, 2023)
Colchicine is used in the treatment of Behçet’s disease, familial Mediterranean fever, gout arthritis, pericarditis, some inflammatory and fibrotic diseases by extracting it as an alkaloid from the plant named Autumn Crocus, which is from the lily family. CA 72-4, which has a glycoprotein structure, is especially useful in the diagnosis and follow-up of gastrointestinal adenocarcinomas as well as its serum level can be increased in pancreatic, ovarian, endometrial, and breast cancers. No drugs that cause CA 72-4 rise have been reported to date. In this article, four patients who were referred to our clinic because of CA 72-4 serum elevation and who used colchicine for various reasons are presented.